"We are not stray leaves blowing about in the wind": exploring the impact of Family Wellbeing empowerment research, 1998-2021 - Nirukshi Perera; Komla Tsey; Marion Heyeres; Mary Whiteside; Leslie Baird; Janya McCalman; Yvonne Cadet-James; Bianca Calabria; Michael Hamilton; Li Yan; Ines Zuchowski; Kearrin Sims; et al. (BMC, 2022)
Abstract Background An Aboriginal-developed empowerment and social and emotional wellbeing program, known as Family Wellbeing (FWB), has been found to strengthen the protective factors that help Indigenous Australians to deal with the legacy of colonisation and intergenerational trauma. This article reviews the research that has accompanied the implementation of the program, over a 23 year period. The aim is to assess the long-term impact of FWB research and identify the key enablers of research impact and the limitations of the impact assessment exercise. This will inform more comprehensive monitoring of research impact into the future. Methods To assess impact, the study took an implementation science approach, incorporating theory of change and service utilisation frameworks, to create a logic model underpinned by Indigenous research principles. A research impact narrative was developed based on mixed methods analysis of publicly available data on: 1) FWB program participation; 2) research program funding; 3) program outcome evaluation (nine studies); and 4) accounts of research utilisation (seven studies). Results  Starting from a need for research on empowerment identified by research users, an investment of $2.3 million in research activities over 23 years produced a range of research outputs that evidenced social and emotional wellbeing benefits arising from participation in the FWB program. Accounts of research utilisation confirmed the role of research outputs in educating participants about the program, and thus, facilitating more demand (and funding acquisition) for FWB. Overall research contributed to 5,405 recorded participants accessing the intervention. The key enablers of research impact were; 1) the research was user- and community-driven; 2) a long-term mutually beneficial partnership between research users and researchers; 3) the creation of a body of knowledge that demonstrated the impact of the FWB intervention via different research methods; 4) the universality of the FWB approach which led to widespread application. Conclusions The FWB research impact exercise reinforced the view that assessing research impact is best approached as a "wicked problem" for which there are no easy fixes. It requires flexible, open-ended, collaborative learning-by-doing approaches to build the evidence base over time. Steps and approaches that research groups might take to build the research impact knowledge base within their disciplines are discussed.